2019
DOI: 10.3390/ma12121952
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Materials for High-Performance Sodium-Ion Batteries

Abstract: Sodium ion batteries (SIBs) are being billed as an economical and environmental alternative to lithium ion batteries (LIBs), especially for medium and large-scale stationery and grid storage. However, SIBs suffer from lower capacities, energy density and cycle life performance. Therefore, in order to be more efficient and feasible, novel high-performance electrodes for SIBs need to be developed and researched. This review aims to provide an exhaustive discussion about the state-of-the-art in novel high-perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 326 publications
(388 reference statements)
0
30
0
Order By: Relevance
“…At the same time, the technology of sodium‐ion batteries (SIBs) is still not mature, particularly the development of new electrode components represents a crucial issue. Many different materials have been investigated ranging from alloy, to carbon‐based systems, and transition metal oxides . Between them ilmenite (FeTiO 3 ), has been recently proposed as possible negative electrode material for lithium and sodium‐ion batteries and for sodium‐ion supercapacitor thanks to the high theoretical capacity, chemical stability and low cost.…”
Section: Introductionmentioning
confidence: 92%
“…At the same time, the technology of sodium‐ion batteries (SIBs) is still not mature, particularly the development of new electrode components represents a crucial issue. Many different materials have been investigated ranging from alloy, to carbon‐based systems, and transition metal oxides . Between them ilmenite (FeTiO 3 ), has been recently proposed as possible negative electrode material for lithium and sodium‐ion batteries and for sodium‐ion supercapacitor thanks to the high theoretical capacity, chemical stability and low cost.…”
Section: Introductionmentioning
confidence: 92%
“…Below we extract the main topics and points. Readers interested in more detail are referred to specific overviews on Na-ion batteries [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Sodium-ion Batteriesmentioning
confidence: 99%
“…Whereas graphite cannot accommodate Na + ions, graphene can provide larger interlayer distances to store a larger number of Na + ions. 225,226 Wang et al reported rGO as an anode in SIBs for the first time in 2013. 225 The as synthesized rGO allowed significant Na + ion insertion because of its large interlayer distances (B0.371 nm) and disordered structures.…”
Section: Na-ion Batteries (Sibs)mentioning
confidence: 99%